Comprehensive Research on the ways to Minimize the Disparity of Sentences in Similar Offences in the Malaysian Criminal Justice System - Yichen Pan; Wong Jun Hao (West Science Law and Human Rights, 2023)
The Malaysian Criminal Justice System, like many others globally, faces the challenge of minimizing sentence disparities in cases involving similar offenses. This comprehensive research endeavor delves into the multifaceted issue of sentencing disparities, seeking to understand its root causes and to propose practical strategies for mitigation. The paper begins by acknowledging the importance of consistent and fair sentencing in upholding the principles of justice and ensuring public trust in the legal system. It highlights the current disparities observed in the sentencing of individuals convicted of similar offenses, by taking theft cases to shed light on the implications for equity, deterrence, and offender rehabilitation. This research adopts a multidisciplinary approach, drawing from legal analysis, case studies, and empirical data to explore the factors contributing to sentencing disparities. Afterward, it presents a range of potential solutions aimed at reducing sentence disparities in the Malaysian context, which includes setting clear sentencing guidelines; implementing Artificial Intelligence Judgement (AI judgment), and setting specialized courts in the criminal justice system. This comprehensive research endeavor aspires to contribute significantly to the ongoing discourse surrounding equitable sentencing practices in Malaysia, fostering a more fair and transparent criminal justice system for all its stakeholders.